Extraocular muscle diameter in Makurdi, North Central Nigeria: what is normal? - Annongu, Terkimbi I.; Msuega, Chia D.; Mohammad, Hameed O.; Iorpagher, Kator P.; Kator, Chaha; Shagbaor, Ayough N.; Bemgba, Wuave R.; Ojaare, Magaji G. (International Journal of Advances in Medicine, 2021)
Background: Establishing normal values of extra ocular muscle (EOM) diameter is essential in a given population. Factors including race, region, gender and environment affect the normal diameter of the EOM. The aim of the study was to determine the normal sizes of the EOM in a population in the North Central part of Nigeria using computed tomography (CT). Methods: One hundred and eighty-three CT images of patients who underwent craniofacial imaging for other conditions and who met the inclusion criteria were evaluated. The maximum diameters of the EOMs on coronal reformatted CT images which are the superior group (SG) (superior rectus and the levator palpebral), inferior rectus (IR) medial rectus (MR) and lateral rectus (LR) were assessed. Results: The mean values±SD obtained were 3.65±1.13, 3.93±0.94, 3.40±0.67, 3.43±0.92 for SG, 1R, MR, and LR muscles respectively on the right and 3.61±1.07, 3.86±0.92, 3.34±0.70, 3.42±0.08 for SG, IR MR and LR muscles respectively on the left. The order IR>SR>MR>LR of average muscle diameter was obtained. The females in this region showed slightly higher mean values of the diameter of the EOM than the males; however, this was not statistically significant. By age, there was no consistent correlation. Conclusions: The established normal values of the EOM may serve as a reference point for ophthalmologist and for cosmetic surgeons and also will add to the pool of the existing knowledge for academic purposes.